Enriching the Theory of Factor Pricing and Income Distribution in Islamic Perspective (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The paper aims to elaborate  the theory of factor pricing and income distribution in Islamic perspective. We place Sadeqs thought as the benchmark and expand it. Using calculus differential, we construct factor pricing and income distribution under mudharabah scheme, which can describe the behavior of producer (mudhaarib) in making decision on business operation appropriately. The paper can prove mathematically that when Islamic principles are internalized, income distribution becomes more equal. This is expressed in parameters s, 1-s, and 1/1-s, as a share of profit goes to capital owner (shahibulmaal), entrepreneur (mudhaarib) and worker, respectively. The paper also proposes that wage level will be determined not only by perception or the mind set of capital owners and workers on the value of their assets, but also the standing moral of entrepreneurs and capital owners.